INFECTIOUS ENDOCARDITIS CAUSED BY A RARE AGENT BURKHOLDERIA CEPACIAN - N. S. Chipigina; N. Yu. Karpova; N. P. Leontieva; V. I. Evdokimov; N. M. Dubinin; A. S. Dubrovina (Архивъ внутренней медицины, 2018)
Introduction. Infectious endocarditis (IE) caused by microorganisms Burkholderia cepacia is a very rare and poorly characterized form of endocarditis.Material and methods. We observed a case of late prosthetic mitral valve IE caused by Burkholderia cepacia in a 34-year-old patient.Results. A patient with a congenital ventricular septum defect underwent surgery on the heart three times in past, including the resection of mitral valve vegetations due to IE at age 17 and mitral valve replacement plus ventricular septum defect plastic reconstruction at 33 years old. The last was complicated by postoperative purulent sterno-mediastenitis treated by thoracoplasty. 10 months later the fever with chills appeared again, a large vegetation on a mitral valve prosthesis was revealed, and Burkholderia cepacia bacteremia with multidrug resistance to antibiotics was find. After the start of treatment with trimethoprim / sulfamethoxazole, normal temperature was observed, but the course of IE was complicated by thromboembolism with a fatal outcome.Conclusions. Multidrug resistance of the pathogen to antibiotics, including those empirically prescribed for IE, is the main risk factor for the adverse outcome of IE caused by Burkholderia cepacia. The lack of generally accepted recommendations determining the doses of antibiotics prescribed in accordance with the microorganism sensitivity is the problem still present in Burkholderia cepacia IE treatment.